Immune profiles in acute myeloid leukemia bone marrow associate with patient age, T-cell receptor clonality, and survival - Brück, Oscar; Dufva, Olli; Hohtari, Helena; Blom, Sami; Turkki, Riku; Ilander, Mette; Kovanen, Panu; Pallaud, Celine; Ramos, Pedro Marques; Lähteenmäki, Hanna; Välimäki, Katja; El Missiry, Mohamed; et al. (Blood advances, 2020)
The immunologic microenvironment in various solid tumors is aberrant and correlates with clinical survival. Here, we present a comprehensive analysis of the immune environment of acute myeloid leukemia (AML) bone marrow (BM) at diagnosis. We compared the immunologic landscape of formalin-fixed paraffin-embedded BM trephine samples from AML (n = 69), chronic myeloid leukemia (CML; n = 56), and B-cell acute lymphoblastic leukemia (B-ALL) patients (n = 52) at diagnosis to controls (n = 12) with 30 immunophenotype markers using multiplex immunohistochemistry and computerized image analysis. We identified distinct immunologic profiles specific for leukemia subtypes and controls enabling accurate classification of AML (area under the curve [AUC] = 1.0), CML (AUC = 0.99), B-ALL (AUC = 0.96), and control subjects (AUC = 1.0). Interestingly, 2 major immunologic AML clusters differing in age, T-cell receptor clonality, and survival were discovered. A low proportion of regulatory T cells and pSTAT1+cMAF− monocytes were identified as novel biomarkers of superior event-free survival in intensively treated AML patients. Moreover, we demonstrated that AML BM and peripheral blood samples are dissimilar in terms of immune cell phenotypes. To conclude, our study shows that the immunologic landscape considerably varies by leukemia subtype suggesting disease-specific immunoregulation. Furthermore, the association of the AML immune microenvironment with clinical parameters suggests a rationale for including immunologic parameters to improve disease classification or even patient risk stratification. •The AML BM milieu is unique and characterized by immunologic alterations differing from CML, B-ALL, and control BM.•Immune profiles of AML patients are related to patient age, T-cell receptor clonality, and survival. [Display omitted]